Pengaruh Kebiasaan Belajar Efektif dan Lingkungan Teman Sebaya terhadap IPK Mahasiswa Fakultas Ekonomi Universitas Negeri Padang Angkatan 2014, 2015 dan 2016 - Ria Nurul Aini (Jurnal Ecogen, 2018)
This research aims to identify : (1) The influence of learning habit and peer group to learning achievement university student, (2) the influence of peer group to learning achievement university student. (3) the influence of learning habit and peer group to learning achievement university student This research was a descriptive causative with quantitative approach. The subject of this research was all university student at Economic Faculty entered year 2014, 2015 and 2016 and the sampling technique used proportional random sampling. Total sample of this research was 339 university student. The research’s sample test of validity and test of reability. Test of Analysis consisted of normality  test, multi-collinearity test and heteroskedastisity test. Hypothesis test was consisting multiple regression with SPSS version 21 for windows. Research result : (1) have a positive and significant influence between learning ability to learning achievement The University Student at Economic Faculty of Padang State University, (2) have a positive and influence between peer group to learning achievement the University Student at economic Faculty of Padang State University, (3) have postitve and signifiant influence between learning habit and peer group to learning achievement the University Student at Economic Faculty of Padang State University.  Key words : learning habit, peer group, learning achievement (IPK)